Locomotive Syndrome Stage 1 Predicts Significant Worsening of Future Motor Performance: The Prospective Yakumo Study. (3rd October 2019) - Kobayashi, Kazuyoshi; Imagama, Shiro; Ando, Kei; Machino, Masaaki; Tanaka, Satoshi; Morozumi, Masayoshi; Kanbara, Shunsuke; Ito, Sadayuki; Inoue, Taro; Ishiguro, Naoki; Hasegawa, Yukiharu
Abstract : Purpose . Aging of society has increased the need for prolongation of a healthy lifespan through maintenance of physical function. Prediction of future physical function may be possible by screening for stage 1 locomotive syndrome (LS). In this prospective study, we examined the influence of LS stage 1 at baseline (2011) on physical performance after 5 years (2016) in a community-dwelling cohort. Methods . The participants were elderly adults aged >40 years who attended public health checkups as part of the Yakumo Study. LS screening in 2011 and 2016 was performed using the 25-question geriatric locomotive function scale (GLFS-25), the stand-up test, and the two-step test. LS of stage 1 or 2 was defined if the participant met the criteria in any of the three tests. Participants not meeting LS criteria were defined as the no risk group. Physical performance tests (10 m gait time, back muscle strength, 3 m TUG, and maximum stride) were also performed in 2011 and 2016. Results . A total of 113 subjects (49 males, 64 females; average age 65.0 years) were followed from 2011 to 2016. At baseline, 73 (65%) had no risk, 29 (25%) had stage 1 LS, and 11 (10%) had stage 2 LS. Five years later, 51 (45%) had no risk, 45 (40%) had stage 1 LS, and 17 (15%) had stage 2 LS. Of the 73 subjects with no risk at baseline, 23 (32%) had stage 1 LS and 1 (1%) had stage 2 LS after 5 years. The baseline stage 1 LS group had significantly worse physical performance after 5 years, compared to the baseline no risk group (p < 0.05 ). Conclusions . This longitudinal study showed that stage 1 LS screening is important for prevention of motor dysfunction in middle-aged and elderly people.